The factors of email adoption in Small Medium Enterprise (SMEs) in Terengganu / Che Aine Shaheera Che Abdullah, Nurfarhamuliana Mohamad and Nurul Fathia Ede - Che Abdullah, Che Aine Shaheera; Mohamad, Nurfarhamuliana; Ede, Nurul Fathia (2012)
The purpose of this is to investigate the factors of email adoption in Small and Medium Enterprise (SMEs). This research was conducted based on distributing questionnaires to the Small and Medium Enterprise (SMEs). The questionnaire’s design consists of two part which is part I is the demographic profile of respondent and part II is the factor of email adoption. The part II section consists of six factors which are voluntariness, relative advantage, compatibility, image ease of use and facilitating condition. Data were analysed using the SPSS software. The result shows that the adoption of email in SMEs is because email has the relative advantage for the user and organization. The factors of adoption were measure based on different variable and the result from the research indicates that the SMEs want to get advantage from the email adoption in their organization. For the future research the study should be conducted with a wide range of the respondent, not only SMEs but whole organization in Malaysia. Besides factor of adopting email, future research could be conducted to analyze the user satisfaction, advantages and disadvantage of email in the organization. Lastly, in future research, the study of relationship between emails toward the SMEs performance also can be conducted.